Response to the Call: Has This Close Call Been a Wake Up Call? - Furey, Mary; Rixon, Daphne (American Journal of Management, 2021)
This paper uses a case study of a 911 service outage to explore the extent to which telecommunications companies (Telco’s) and governments learn from serious incidents and close calls. The study takes a longitudinal approach to identify initial company and government reactions and then revisits key government stakeholders through interviews and documentary reviews to discern whether any lessons were learned. The research found that although initially the telecommunications company involved in the outage and the local levels of government expressed concern and indicated they would introduce changes to ensure such an incident would not occur again, after more than a decade, there were no changes in government requirements for back-up and disaster recover standards. Clearly, this close call was not a wake-up call.